A Phenomenological Study on the Social Meaning of Costs in the Rambu Solo' Tradition - Faisal, Andi; Syarifuddin, Syarifuddin; Damayanti, Ratna Ayu; Nagu, Nadhirah (Journal of International Conference Proceedings, 2023)
This article aims to explore the social significance of the cost of conducting the Rambu Solo' ceremony from the perspective of the Toraja community. This research was conducted in the traditional region of Kete' Kesu' in North Toraja. The research participants consisted of traditional elders from Kesu' and families who organized the ceremonies. Data was collected through indepth interviews and participatory observations. The phenomenological approach was employed to delve of the expenses. The findings of the study revealed that the Toraja people perceive the expenses to repay the deceased relatives' kindness and as a form of accountability from children/grandchildren to their deceased parents